The relevance of macroeconomic indicators in predicting financial distress of public listed firms in Malaysia / Nur Hidayati Sairin - Sairin, Nur Hidayati (2020)
Financial distress can be defined as an inability of companies to generate profit due to excessive debt. The company that suffers from financial distress will cause them to fail in many business operations that increase their probability of losing their capital from the investors. There is ongoing debate about the relationship of macroeconomic indicators toward financial distress. Concerning the various empirical findings, it has been argued that the ability of macroeconomic indicator can give impact or influence the companies to have financial distress problem or becoming bankrupt. Therefore, the